Halogenation of Peptides and Proteins Using Engineered Tryptophan Halogenase Enzymes - Barindra Sana; Ding Ke; Eunice Hui Yen Li; Timothy Ho; Jayasree Seayad; Hung A. Duong; Farid J. Ghadessy (Biomolecules, 2022)
Halogenation of bioactive peptides via incorporation of non-natural amino acid derivatives during chemical synthesis is a common strategy to enhance functionality. Bacterial tyrptophan halogenases efficiently catalyze regiospecific halogenation of the free amino acid tryptophan, both in vitro and in vivo. Expansion of their substrate scope to peptides and proteins would facilitate highly-regulated post-synthesis/expression halogenation. Here, we demonstrate novel in vitro halogenation (chlorination and bromination) of peptides by select halogenase enzymes and identify the C-terminal (G/S)GW motif as a preferred substrate. In a first proof-of-principle experiment, we also demonstrate chemo-catalyzed derivatization of an enzymatically chlorinated peptide, albeit with low efficiency. We further rationally derive PyrH halogenase mutants showing improved halogenation of the (G/S)GW motif, both as a free peptide and when genetically fused to model proteins with efficiencies up to 90%.